2019
DOI: 10.24036/0201932105397-0-00
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Probiotic Bacteria Candidates in The Mangrove Tourism Area in Klawalu Sorong City West Papua

Abstract: Probiotic bacteria is one of the biological control. It had a role inhibiting or killing pathogenic microorganisms. In addition, it also played a role in improving water quality as in fish maintenance media. The basic principle of probiotics was the utilization of the ability of microorganisms to increase absorption in the digestive tract of fish. Probiotic bacteria were able to produce antimicrobial compounds such as lactic acid, hydrogen peroxide, and bacteriocin. These compounds were antimicrobial and antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Previously, a study was conducted on screening probiotic bacteria candidates in the Klawalu subdistrict, Sorong City, West Papua Province. The results of the study indicated that 9 isolates had potential as lactic acid bacteria (Sukmawati and Badaruddin 2019). However, exploration of nitrogen-fixing bacteria at the genetic level in mangrove ecosystems has not been conducted.…”
Section: Introductionmentioning
confidence: 96%
“…Previously, a study was conducted on screening probiotic bacteria candidates in the Klawalu subdistrict, Sorong City, West Papua Province. The results of the study indicated that 9 isolates had potential as lactic acid bacteria (Sukmawati and Badaruddin 2019). However, exploration of nitrogen-fixing bacteria at the genetic level in mangrove ecosystems has not been conducted.…”
Section: Introductionmentioning
confidence: 96%
“…Amylase enzyme production is influenced by several factors and in general, amylase enzymes are optimally generated at a certain point in the logarithmic phase of the microbial growth curve, but there are certain microbes where the logarithmic phase is longer so that the amylase enzyme is not produced because the point has not been reached so long incubation is influential in this matter (Gunam, et al, 2012;Sukmawati & Badaruddin, 2019 ). The temperature can affect because there are some thermophilic bacteria that are more optimal bacteria in the production of amylase enzymes in higher temperature conditions (Supriyanti & Heryanto, 2013).…”
Section: Figure 1 Standard Curve Of Maltose Solutionmentioning
confidence: 99%
“…According to previous research results, no one has explored probiotic bacteria from mangrove areas. Thus, researchers conducted a bacterial screening as a probiotic candidate in the Klawalu mangrove tourism area of Sorong City, West Papua and found that of the 16 mud and water samples, 11 samples were detected as probiotic bacterial candidates (Sukmawati and Badaruddin, 2019). Furthermore, the study continued by identifying potential probiotic bacteria molecularly and the molecular identification results revealed three potential bacterial isolates as probiotic candidates, namely Bacillus safensis strain C251 SA3, Bacillus amyloliquefaciens strain NO10 SA8 and Bacillus australimaris strain IIHR GAPB01 SL1 (Sukmawati et al, 2022).…”
Section: Introductionmentioning
confidence: 99%